ANALISIS MISKONSEPSI KONSEP STRUKTUR MORFOLOGI TUMBUHAN PADA MAHASISWA PENDIDIKAN BIOLOGI DALAM PERKULIAHAN SISTEMATIKA TUMBUHAN TINGGI TAHUN AJARAN 2016/2017 - Sari, Tanti Yunita; Fauziah, Yuslim; Syafi’i, Wan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research is to know the Misconception Concept of Plant Morphology Structure in Biology Education Student in Higher Systematic Lecture of Academic Year 2016/2017. This research is a descriptive research. This research was conducted in June 2017. The sample in this study is all students of class 2015/2016 which is a fourth semester students who follow the course of Systematics of High Plants which amounted to 91 people. The technique in determining the sample is the total sampling. The results show that misconception is still found in all concepts of plant morphology structure with percentage of 43%. Misconceptions on the concept of plant morphology are included in the medium category. The highest misconception occurred on the concept of stem with percentage of 55%, followed by percentage of misconception on root concept with 49% percentage, then misconception on leaf morphology concept with percentage 47%, then fruit morphology concept with percentage 45%, flower morphology concept with percentage 40% , The morphological concept of seeds with percentage of 37% and last percentage of the lowest misconception on the concept of life forms and the general form of plants with a percentage of 30%. The conclusion of the research is Misconception on the Concept of Plant Morphology Structure In Biology Education Students in Higher Systematic Lecture is still found in all concepts with medium category.Â Keywords: Misconception, Plant Morphology Structure Concept, High Plant Systematics